Pharmacovigilance Bibliometrics: Visualizing Thematic Development in the Category of Pharmacology and Pharmacy in Web of Science - Wang, Li; Feng, Wanyu; Duan, Jingli; Liang, Jun (Frontiers in Pharmacology, 2021)
Introduction: Pharmacovigilance studies include monitoring and preventing the occurrence of new, rare or serious adverse drug reactions, making it possible to discover new safety issues without delay. Bibliometrics could assist scholars to analyze the development of pharmacovigilance. Methods: The MeSH terms of both pharmacovigilance and “adverse drug reaction reporting system” were retrieved in the Science Citation Index Expanded. Articles from 1974 to July 2021 in the Pharmacology and Pharmacy category were recruited. The citation reports including publication numbers, h-index, sum and average cited times in terms of annuals, countries, organizations, authors and journals were tabulated. The co-authorship relations in the analysis units of countries, organizations and authors, the top 10 burst references, the document citation network, and the author’s keywords co-occurrence overlay map were visualized by bibliometric software including website (https://bibliometric.com/), VOSviewer, CiteSpace, and CitNetExplorer. Results: From 1974 to the present, the most high-yield year, country, institute, author, and journal were 2020 (n=222), France (n=522), Netherlands Pharmacovigilance Centre Lareb (n=82), Jean-Louis Montastruc (n=125), Drug Safety (n=384), respectively in all 2128 articles. USA, Institut National de la Sante et de la Recherche Medicale, and Jean-Louis Montastruc had the most co-authorship strength at the macro (global), meso (local), and micro (individual) levels. The topics of burst references covered the development of methodology, issues of patients reporting and under-reporting, evaluation of methods and database, assessment of causality, and perspectives in pharmacovigilance. Eight clusters were grouped in the document citation network. ‘Pharmacovigilance’, ‘adverse drug reactions’, ‘pharmacoepidemiology’, ‘drug safety’, and ‘signal detection’ were the research priorities, while ‘drug-related side effects and adverse reactions’, ‘VigiBase’, ‘disproportionality analysis’, ‘social media’, ‘FAERS’, ‘chemotherapy’, ‘patient safety’, ‘reporting odds ratio’ and ‘preventability’ might be the future research hotspots. Conclusion: Positive synergies can be observed in this study by employing the multiple software tools which established relationship between the units of analysis. The bibliometric analysis can organize the thematic development and guide the hotspots of pharmacovigilance in Pharmacology and Pharmacy.